2012
DOI: 10.1111/j.1365-2583.2012.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of redox homeostasis leads to oxidative DNA damage in spermatocytes of Wolbachia‐infected Drosophila simulans

Abstract: Molecular interactions between symbiotic bacteria and their animal hosts are, as yet, poorly understood. The most widespread bacterial endosymbiont, Wolbachia pipientis, occurs in high density in testes of infected Drosophila simulans and causes cytoplasmic incompatibility (CI), a form of male‐derived zygotic lethality. Wolbachia grow and divide within host vacuoles that generate reactive oxygen species (ROS), which in turn stimulate the up‐regulation of antioxidant enzymes. These enzymes appear to protect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 94 publications
7
66
0
Order By: Relevance
“…Stimulation of excess reactive oxygen species (ROS) has been reported previously in Drosophila infected by Wolbachia (23).…”
mentioning
confidence: 99%
“…Stimulation of excess reactive oxygen species (ROS) has been reported previously in Drosophila infected by Wolbachia (23).…”
mentioning
confidence: 99%
“…Wolbachia infection of Aedes spp. and Drosophila simulans leads to elevated levels of transcripts of genes encoding enzymes involved in the production of ROS in their host's cells (Brennan et al 2012;Pan et al 2011). This increase is similar to that seen with infections by the closely related Rickettsia bacteria, in which H 2 O 2 is formed at a level that causes host cell injury (Pan et al 2011).…”
Section: Discussionmentioning
confidence: 83%
“…Increased reactive oxygen species corresponds with Toll pathway restriction of DENV infection and it has been suggested that Wolbachia mediates anti-DENV protection via the Toll pathway [49 ]. Excess reactive oxygen species are also stimulated in Drosophila naturally infected by Wolbachia [55]. The regulation of iron metabolism of Drosophila is altered in the presence of Wolbachia [51 ,56,57] and increases in dietary iron have been linked to an increase in oxidative stress and increased Wolbachia density [58].…”
Section: Mechanisms Of Wolbachia-mediated Antiviral Protectionmentioning
confidence: 98%